Transition metal complexes with sulfur ligands Part CXLIV. Square planar nickel complexes with NiS 4 cores in three different oxidation states: Synthesis, X-ray structural and spectroscopic studies - Sellmann, Dieter; Binder, H.; Häußinger, Daniel; Heinemann, Frank Wilhelm; Sutter, Jörg (Inorganica Chimica Acta, 2000)
The reaction of 'S-bu(2)'(2-) = 3,5-ditertiarybutyl-1,2-benzenedithiolate(2 -) with Ni(ac)(2). 4H(2)O and subsequently AsPh4Cl, yielded (AsPh4)(2)[Ni('S-bu(2)')(2)] (1). Complex 1 is extremely air sensitive and oxidized rapidly to give (AsPh4)[Ni('S-bu(2)')(2)] (2). The anion of 2 could be further oxidized by iodine to give neutral [Ni('S-bu(2)')(2)] (3). Complexes 1, 2 and 3 contain nickel in the formal oxidation states + 2, + 3 and + 4, and could be completely characterized by X-ray structure determination and spectroscopic methods. The results indicate that the oxidation of 1–>2–>3 concerns electrons residing in molecular orbitals having [NiS4] character. No evidence could be obtained for an involvement of the benzene rings or an electron delocalization beyond the [NiS4] core. This conclusion corresponds with the reactivity of 3 versus 2 and 1 towards protons and CO. While 3 is inert to the attack of H+ and CO, 2 and 1 exhibit rapid reactions to give 'S-bU(2)'-H-2 and either nickel-chioro complexes or Ni(CO)(4). (C) 2000 Elsevier Science S.A. All rights reserve
Keywords: nickel thiolate complexes; high oxidation states